The Carter the story of Lil Wayne - Lil Wayne 1982- (Revolver Entertainment, 2011)
Step into the life of multi-Grammy award-winning rapper Dwayne Michael Carter Jr., aka Lil' Wayne. This mind-blowing, cinematic journey delves into the thoughts and world of an extremely talented musician whose creative force is something to behold. With unbelievable access to Lil' Wayne's public and private lives, the film captures remarkably candid moments about his life and work